Governing by Numbers and Human Capital in Education Policy Beyond Neoliberalism Social Democratic Governance Practices in Public Higher Education - Madsen, Miriam (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book addresses governing by numbers and human capital policy in higher education by asking how higher education is quantified, how the quantitative information is used in educational governance, and how the information is perceived by students, teachers, managers, and policymakers, and affects decision-making. It also thematically discusses how human capital theory affects the quantification practices and, thereby, their effects. Based on these analyses, the book asks whether governing by numbers and human capital in education policy are necessarily neoliberal practices, and thus questions the theory of global convergence in educational governance.The book provides a thorough analysis of the quantification of graduate outcomes based on the philosophical framework of Agential Realism, thus offering a novel analytical approach to the study of data and indicators in educational governance. The book draws on a comprehensive ethnographic case study from Danish higher education, and relates the findings from this case study to empirical cases in other countries and international research in the field. The book brings together literature from various fields, including political science, accounting, education, and sociology of quantification, in order to provide a comprehensive account of how quantification practices affect education.
Part 1. Introduction -- Chapter 1. The rise of outcome indicators in educational governance -- Chapter 2. Methodological approaches: Studying graduate outcome metrics and educational governance -- Part 2. Quantification practices: Human capital and the value of higher education -- Chapter 3. Quantifying higher education with graduate outcome metrics -- Chapter 4. Graduate outcome metrics and the economization of education -- Part 3. Governance practices: Indicators, hierarchical pressures, and temporal-affective effects -- Chapter 5. Calculative governance instruments -- Chapter 6. The governing properties of numbers -- Part 4. Data reception: Subjectivities and amplified resource inequalities -- Chapter 7. Subjectivizing effects of graduate outcome data -- Chapter 8. Educational development effects of graduate outcome metrics -- Part 5. Conclusion -- Chapter 9. Governance hybridity and its implications for education and research on educational governance.
Keywords: Education and state; Education, Higher; Educational sociology; Public administration; Educational Policy and Politics; Higher Education; Sociology of Education; Public Administration